Clostridium butyricum partially regulates the development of colitis-associated cancer through miR-200c - Xiao, Y.; Dai, X.; Li, K.; Gui, G.; Liu, J.; Yang, H. (Cellular and Molecular Biology, 2017)
Colitis-associated cancer (CAC), one form of colorectal cancer (CRC),is an increasing concern worldwide. Both diagnosis and current therapy are challenging and bottlenecked. The aim of this study is to investigate novel mechanisms by which the therapeutic C. butyricum regulates colitis-induced oncogenesis. Mouse models of CAC were established with 2,4,6-Trinitrobenzenesulfonic acid (TNBS)and azoxymethane (AOM), following by biochemical, clinical and histological analysis. The integrity of epitheliumwas examined by electron microscopy (EM). The epithelial barrier function was evaluated with Ussing chamber. Real time PCR and fluorescent in situ hybridization (FISH) were performed to characterize the effect of C. butyricum on miR-200c; cell proliferation assays (MTT) were performed to study the role ofC. butyricum on epithelial cell proliferation mediated by miR-200c inhibitor; finally, we quantified the proinflammatory cytokines TNF-Î± and interleukin (IL)-12 by real time PCR. C. butyricum ameliorates clinical, histological and biochemical manifestations in colitis-induced CAC models. Further mechanistic studies demonstrated that C. Butyricum could lengthen epithelial microvillus and increase TER by decreasing the transepithelial permeability. We also showed that C. butyricum facilitates the expression of miR-200c, by which increase the proliferation rate. Finally, we found that C. butyricum can regulate the production of proinflammatory cytokines TNF-Î± and IL-12 through miR-200c. C. butyricum may regulate epithelial barrier function through miR-200c, then to be involved in the process of inflammation-associated cancers.